Основні доктринальні підходи до розуміння функції «хранителя» конституції Президента Республіки Польща - Марчук, М. І.; Marchuk, M. I.; Марчук Микола Іванович (Науковий вісник Ужгородського Національного Університету. Сер.: Право. – 2022. – Вип. 72, ч. 2. – С. 241-246, 2022)
У статті окреслюються основні доктринальні підходи до розуміння ролі Президента Республіки Польща щодо охорони Конституції Польської держави. Констатується, що попри той факт, що охорона Конституції законодавчо визнається однією із ключових функцій Президента Республіки Польща як глави держави, у польській конституційній доктрині відсутнє чітке бачення реального наповнення даної функції відповідними повноваженнями. Акцентується, що дана ситуація обумовлена наявним у Польщі різновидом республіканської форми правління та специфікою польської моделі поділу влад. Доводиться, що тлумачення Конституції, яке міститься в офіційних актах, виданих Президентом, має перевагу над тлумаченням інших державних органів щодо повноважень, які здійснюються цими органами, а також коли між Президентом та іншим центральним конституційним органом держави трапляються суперечливі або навіть конфліктні ситуації. Зроблено висновок, що із функції «хранителя» Конституції випливає «презумпція правоти» Президента Республіки Польща перед іншими органами влади. Зазначається, що лише винесення Конституційним Трибуналом остаточного рішення щодо компетенційної суперечки може скасувати тлумачення Президента, спростовуючи його інтерпретацію відповідних положень Конституції, що ґрунтується на конкретних преференціях тлумачення Президента як «хранителя Конституції». Підкреслюється, що нагляд Президента Республіки Польща за дотриманням Конституції, очевидно, також означає особливу турботу про дотримання Конституції самим Президентом як невід’ємною інституційною складовою системи органів державної влади. Резюмується, що конкретизація і доповнення принципу легалізму, вираженого у ст. 7 Конституції Республіки Польща, викладена у ч. 3 ст. 126, невипадково міститься в тій самій статті, що і положення ч. 1 та 2, визначаючи основні функції (завдання) Президента. Тому Президент Республіки Польща як «хранитель» Конституції може виконувати ці та інші передбачені законом функції, причому не лише на основі повноважень, визначених у конкретних положеннях Конституції та законів, а й на основі уповноважуючих норм, системно сконструйованих на основі конституційних або законодавчих положень.

The article outlines the main doctrinal approaches to understanding the role of the President of the Republic of Poland in protecting the Constitution of the Polish state. It is stated that despite the fact that the protection of the Constitution is legally recognized as one of the key functions of the President of the Republic of Poland as the head of state, the Polish constitutional doctrine lacks a clear vision of the actual filling of this function with relevant powers. It is emphasized that this situation is due to the type of republican form of government in Poland and the specifics of the Polish model of the separation of powers. It is proved that the interpretation of the Constitution, which is contained in the official acts issued by the President, has priority over the interpretation of other state bodies regarding the powers exercised by these bodies, as well as when there are contradictory or even conflicts between the President and another central constitutional body of the state situations It was concluded that the function of the “custodian” of the Constitution results in the “presumption of rightness” of the President of the Republic of Poland in front of other authorities. It is noted that only a final decision by the Constitutional Tribunal on the competence dispute can cancel the interpretation of the President, refuting his interpretation of the relevant provisions of the Constitution, which is based on the specific preferences of the interpretation of the President as the “guardian of the Constitution”. It is emphasized that the supervision of the President of the Republic of Poland over the observance of the Constitution obviously also means a special concern for the observance of the Constitution by the President himself as an integral institutional component of the system of state authorities. It is summarized that the specification and addition of the principle of legalism expressed in Art. 7 of the Constitution of the Republic of Poland, set out in Part 3 of Art. 126, it is no coincidence that it is contained in the same article as the provisions of parts 1 and 2, defining the main functions (tasks) of the President. Therefore, the President of the Republic of Poland, as the “custodian” of the Constitution, can perform these and other functions provided for by law, and not only on the basis of the powers defined in specific provisions of the Constitution and laws, but also on the basis of authorizing norms systematically constructed on the basis of constitutional or legislative provisions.

В статье указываются основные доктринальные подходы к пониманию роли Президента Республики Польша по охране Конституции Польского государства. Констатируется, что, несмотря на тот факт, что охрана Конституции законодательно признается одной из ключевых функций Президента Республики Польша как главы государства, в польской конституционной доктрине отсутствует четкое видение реального наполнения данной функции соответствующими полномочиями. Акцентируется, что данная ситуация обусловлена ​​имеющимся у Польши – разновидностью республиканской формы правления и спецификой польской модели разделения властей.
Basic doctrinal approaches to understanding the function of the “custodian” of the constitution of the President of the Republic of Poland
Keywords: Конституційне право. Constitutional Law. Конституционное право; Наукові публікації. Scientific publications. Научные публикации; зарубіжний досвід; зарубежный опыт; Польща; хранитель; Конституція; державна влада; президент; Конституция; государственная власть; Польша; Constitution; state power; Poland